2016
DOI: 10.3390/nu8040243
|View full text |Cite
|
Sign up to set email alerts
|

Long Chain Omega-3 Polyunsaturated Fatty Acid Supplementation Alleviates Doxorubicin-Induced Depressive-Like Behaviors and Neurotoxicity in Rats: Involvement of Oxidative Stress and Neuroinflammation

Abstract: Doxorubicin (DOX) is a chemotherapeutic agent widely used in human malignancies. Its long-term use can cause neurobiological side-effects associated with depression. Omega-3 polyunsaturated fatty acids (ω-3 PUFAs), the essential fatty acids found in fish oil, possess neuroprotecitve and antidepressant activities. Thus, the aim of this study was to explore the potential protective effects of ω-3 PUFAs against DOX-induced behavioral changes and neurotoxicity. ω-3 PUFAs were given daily by gavage (1.5 g/kg) over … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
49
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(53 citation statements)
references
References 44 publications
3
49
1
Order By: Relevance
“…Our previous studies have confirmed that n -3 fatty acids possess broad spectrum of neuroprotective activities in both in vitro and in vivo experiments because of their anti-oxidant and anti-inflammatory properties [61,62,63,64,65,66]. Additionally, Wu et al [67] showed that n -3 PUFAs significantly attenuated the gene expression of pro-inflammatory cytokines, including IL-1β, IL-6, and TNF-α, and the protein levels of NF-κB and iNOS in brain tissues of rats with doxorubicin-induced depressive-like behaviors and neurotoxicity. In another in vivo study, Taepavarapruk and Song [48] revealed that n -3 PUFAs improved memory through IL-1-glucocorticoid-ACh release and IL-1-NGF-ACh release pathways.…”
Section: Discussionmentioning
confidence: 73%
“…Our previous studies have confirmed that n -3 fatty acids possess broad spectrum of neuroprotective activities in both in vitro and in vivo experiments because of their anti-oxidant and anti-inflammatory properties [61,62,63,64,65,66]. Additionally, Wu et al [67] showed that n -3 PUFAs significantly attenuated the gene expression of pro-inflammatory cytokines, including IL-1β, IL-6, and TNF-α, and the protein levels of NF-κB and iNOS in brain tissues of rats with doxorubicin-induced depressive-like behaviors and neurotoxicity. In another in vivo study, Taepavarapruk and Song [48] revealed that n -3 PUFAs improved memory through IL-1-glucocorticoid-ACh release and IL-1-NGF-ACh release pathways.…”
Section: Discussionmentioning
confidence: 73%
“…PUFAs perform myriad physiological functions crucial to normal brain maturation and functioning, including: 1) activation of membrane receptors such as the peroxisome proliferator-activated receptors (PPAR) α and γ, and G-protein coupled surface receptor 32 (GPR32), thereby modulating gene expression; 2) regulation of brain glucose uptake and glucose receptor (GLUT1) density; 3) modulation of the endocannabinoid system; 4) production of active pro- or anti-inflammatory metabolites, namely eicosanoids, leukotrienes, and docosanoids; and 5) incorporation into membrane phospholipids, thereby affecting membrane physico-chemical properties and functioning of membrane-bound proteins, such as ion channels and receptors (reviewed in [46]). Long-chain omega-3 PUFAs may have a role in neuroprotection due to their anti-oxidative [79], anti-inflammatory [1012] and anti-apoptotic [1315] properties.…”
Section: Introductionmentioning
confidence: 99%
“…EPA and DHA are substrates for lipid mediators important in the inflammatory response, many of which have a wide range of anti-inflammatory and pro-resolving actions [19]. In a recently published report, administration of EPA and DHA concurrently with doxorubicin chemotherapy prevented depressive-like behaviors and reduced neuroinflammation, oxidative stress, and neural apoptosis in male rats [20]. DHA has been shown to be safe and well tolerated at a dose of 1.8 g/day in women with advanced metastatic breast cancer during 20 weeks of doxorubicin-based chemotherapy, and DHA was associated with improved overall survival in a subset of women who highly incorporated DHA into plasma phospholipids [21].…”
Section: Effects Of Chemotherapy In the Brainmentioning
confidence: 99%
“…Recently, the effects of n-3 FAs on depressive-like behavior in male rats treated with doxorubicin (DOX) have been examined [20]. Rats in the DOX + n-3 FA group were given EPA and DHA (1.5 g/kg) by gavage beginning one week prior to chemotherapy administration and continuing for two weeks during seven injections of doxorubicin (2.5 mg/kg dose).…”
Section: Effects Of Chemotherapy In the Brainmentioning
confidence: 99%